2020
DOI: 10.1093/deafed/enaa035
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Anxiety Symptoms in Australian Deaf or Hard of Hearing Children

Abstract: Deaf/deaf or hard of hearing (DHH) children are at an increased risk of developing mental health problems, with growing evidence that they may experience greater anxiety symptoms than hearing peers. The present study investigated whether Australian children with varying degrees of hearing loss experienced increased anxiety symptoms compared to hearing children. Furthermore, we examined whether child anxiety symptoms were associated with known risk factors including psychological symptoms of anxiety and depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Parents and other caregivers are confronted with the challenge of acquiring new knowledge and abilities and figuring out how to use what they have learned in their everyday lives. Long, Attuquayefio, and Hudson (2021) have found that to make matters worse, if English is not the dominant language in the houses of these parents and their children, parents may need an interpreter while speaking with them the audiologist and other intervention specialists. Access to health information in various forms (e.g., verbal, written, demonstration, video) may help patients and their families retain knowledge and build good self-management skills.…”
Section: Chart 1: Website Resultsmentioning
confidence: 99%
“…Parents and other caregivers are confronted with the challenge of acquiring new knowledge and abilities and figuring out how to use what they have learned in their everyday lives. Long, Attuquayefio, and Hudson (2021) have found that to make matters worse, if English is not the dominant language in the houses of these parents and their children, parents may need an interpreter while speaking with them the audiologist and other intervention specialists. Access to health information in various forms (e.g., verbal, written, demonstration, video) may help patients and their families retain knowledge and build good self-management skills.…”
Section: Chart 1: Website Resultsmentioning
confidence: 99%
“…To our knowledge, this is the first report on the STAI test performed on hearing-impaired youth. Recently, [30] undertook a prospective longitudinal investigation of an association between hearing loss and anxiety using STAI, but the study population was composed of subjects aged 65 and above. As a result, the authors established the hypothesized association, and social isolation along with communication difficulties was suggested as possible contributing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Children with special needs are at risk of experiencing social anxiety (Jones et al , 2014), one of which is deaf children in the mild or moderate hearing impairment group, hearing impairment (Contrera et al , 2017), the cause of the feeling of loneliness (Shoham et al , 2019), sensitive (Viola Safira Rohmatika, 2018), difficulty building social relationships and adapting (Long et al , 2021) and chance to experience bullying (Damayanti et al , 2016; Sakinah and Marlina, 2018). This has an impact on psychological aspects such as a decrease in self-esteem that will make individuals withdraw from the social environment, anxiety disorders and depression to suicidal ideation (Ikhsani, 2015).…”
Section: Introductionmentioning
confidence: 99%